A configuração do grupo escolar Júlio Bueno Brandão no contexto republicano (Uberabinha - MG, 1911-1929) - Carvalho, Luciana Beatriz de Oliveira Bar de (2002)
It is a research in the thematic area of History of the Education, with objective of apprehending the process of constitution of the School Group Júlio Bueno Brandão, in the period from 1911 to 1929, in Uberabinha-MG. We tried to understand the historicaleducational accustom of republican Brazil, with the intention of identifying, in this context, the transformations for the which it passed the Brazilian society, as well as the educational reforms that they were carried on by the Republic, in the attempt of minimizing the indexes of illiteracy blemishes of the image of the country that, at the same time, they impeded its march heading for the civilization. In this sense, we accomplished a study about the educational situation of Uberabinha-MG, objectifying to find elements that subsidized our discussion around the concern of creating, in the city, the republican consent. As sources in the our supply of statistical data collected the annuals of the IBGE, the executive's ordinance-laws and articles of local newspapers close to, A Tribuna e o Progresso. It was looked for, like this, to analyze to what extent the School Group Júlio Bueno Brandão, influenced to the propagation and consolidation of the republican concept in the city, because the education for the Old Republic, appears as one of the civilization roads , when forming the citizen for the democratic Republic, projecting, to the country, the possibility to be close to the developed nations.